Wellbeing in Winter: Testing the Noticing Nature Intervention During Winter Months - Passmore, Holli-Anne; Yargeau, Alissa; Blench, Joslin (Frontiers in Psychology, 2022)
The main objective of this two-week RCT study was to test the efficacy of the previously developed Noticing Nature Intervention (NNI) to boost wellbeing during winter months. The NNI consists of noticing the everyday nature encountered in one’s daily routine, and making note of what emotions are evoked. Community adults (N = 65) were randomly assigned to engage in the NNI, or were assigned to one of two control conditions. Paired t-tests revealed significant increases pre- to post-intervention in the NNI group for positive affect (d = 0.43), elevation (d = 0.59), nature connectedness (d = 0.46), and hope agency (d = 0.64), and a marginally significant increase in transcendent connectedness (d = 0.41). No significant pre-post difference emerged for any aspect of wellbeing in the control conditions. Analysis of qualitative findings revealed that negative emotional themes were 2.13 times more likely to be associated with built photos than with nature photos. Feelings of peace, awe, happiness, humbleness, and hope were more likely to associated with nature photos, while feelings of annoyance, loneliness, curiosity, uncertainty, anger, yearning, and comfortableness were more likely to be associated with built photos. Overall, results not only bolster previous findings regarding the efficacy of the NNI, they also suggest that engaging in the NNI can provide a boost to positive affect, elevation, and hope even in the cold of winter. This study is the first (to our knowledge) to test any nature-based wellbeing intervention during colder, winter months, and to directly assess the impact of a nature-based wellbeing intervention on levels of hope.